064 Preserving vision by optimising surveillance of suprasellar lesions, a consensus statement. Issue 6 (27th May 2022) - Gilmartin, Aisling; Nowak, Victoria; Marcus, Hani; Grieve, Joan; Dorward, Neil; Petzold, Axel; Acheson, James; Baldeweg, Stephanie; Bremner, Fion; Khaleeli, Zhaleh; ,
Abstract : Introduction: Suprasellar tumours are a heterogenous group which may compromise the optic apparatus. Serial monitoring and timely intervention preserves vision, but consensus regarding optimal surveillance is lacking. An audit at our tertiary centre found that variation in surveillance intervals and methods leads to under- and over-investigation. We present a novel, evidence- and consensus- based guideline for efficient neuro-ophthalmological monitoring of this cohort. Method: We searched MEDLINE/Pubmed for 'visual field', 'visual acuity', 'pituitary' and 'macroadenoma' with filters: Clinical trial, Meta-analysis, Randomised Control Trial, Review, Systematic review (2000–2020). We constructed a guideline which was reviewed by the multidisciplinary pituitary network consultants (neurosurgery, endocrinology, neuro-ophthalmology). Results: We found 18 relevant publications covering pre- and post-operative tumour evaluation. We recommend visual acuity, colour vision, 24–2 Humphrey Visual Field and OCT assessment in a technician- led clinic, supervised by a named neuro-ophthalmology consultant. We recommend baseline and post- operative assessment, then annual for 5 years, progressing to every 2 years. We suggest how to identify patients who may be safely discharged and those requiring re-referral. Conclusion: A clear and simple guideline for neuro-ophthalmology surveillance of suprasellar lesions is proposed to optimise safety, efficiency and effectiveness. The guideline will be validated in future through departmental audit. aisling: gilmartin@nhs.net 57